Information, deformed κ-Wehrl entropies and semiclassical delocalization - Pennini, Flavia (2009)
Semiclassical delocalization in phase space constitutes a manifestation of the Uncertainty Principle, one indispensable part of the present understanding of Nature and the Wehrl entropy is widely regarded as the foremost localization-indicator. We readdress the matter here within the framework of the celebrated semiclassical Husimi distributions and their associatedWehrl entropies, suitably κ-deformed. We are able to show that it is possible to significantly improve on the extant phase-space classical-localization power.